Pengaruh Kerjasama Tim, Kompetensi dan Birokrasi Terhadap Kinerja Anggota Satlantas Polrestabes Semarang dengan Kepuasan Kerja sebagai Variabel Intervening - Hamdito, Octaviangga; Indarto, Indarto; Budiati, Yuli (Jurnal Litbang Polri, 2025)
Traffic Police have duties and functions in enforcing traffic discipline regulations and improving traffic awareness. This research purposes determining factors that can improve the performance of police members of the Semarang Police traffic unit. The variables in this research are teamwork, competence and bureaucracy, the dependent variable is performance with the intervening job satisfaction as mediating variable. This research is conducted through quantitative methods using questionnaires as data collecting. Around 58 police members of the Semarang Traffic and Police Traffic Unit participated in this study. The path analysis is used with support by SmartPLS program. The results show that teamwork, competence and bureaucracy influence performance and job satisfaction. However, job satisfaction has no effect on performance and has not succeeded in becoming an intervening variable in this research.